Kajian Nilai-Nilai Pendidikan Agama Hindu Dalam Teks Geguritan Wirata Parwa Pada Masyarakat Banjar Pakraman Batannyuh Tabanan - I Made Pasek Gelgel Sukerna (Cetta: Jurnal Ilmu Pendidikan, 2019)
Geguritan is one of Hindu literary works that pack a lot of Hindu religious education values that can be used as guidelines and demands in everyday life. One of them is the Geguritan Wirata Parwa which is classified as Ithiasa which in it is packed a lot of Hindu religious education values such as: tattwa, susila and acara. There fore, to be able to dig and find the values contained in the text of Geguritan Wirata Parwa, it is necessary to conduct in depth study through a scientific research that aims to interpret every essence of teaching and values contained therein appropriately.